"Small streams make big rivers" : Possibilities and limitations in implementing Education for Sustainable Development in Finnish lower secondary schools - Kotipelto, Suvipilvi (My University, 2023)
The purpose of this master’s thesis was to investigate the implementation of Education for Sustainable Development (ESD) in Finnish lower secondary schools. The research was interested in what kind of resources were available for subject teachers, principals, and education experts in implementing ESD. Furthermore, the aim of the research was to investigate subject teachers, principals, and education experts’ possibilities and limitations of their actions, which was conceptualized through the theory of professional agency. Lastly, the thesis examined what supported the possibilities in implementing ESD and what kind of support was still missing. The qualitative data consisted of thematic semi-structured interviews with subject teachers, and a principal in lower secondary schools in the Turku area, as well as education experts at the Finnish National Agency for Education. The interviews were conducted in the spring 2021, and the data was analysed using thematic analysis. The main findings indicated that teachers, principals, and education experts had a significant number of various resources available. However, their own activity and initiative played a considerable role in what kind of information they found and how they used it. The perceived professional agency was rather strong with all the interviewees, and they described having good possibilities to influence and implement ESD. For the teachers, the main ways of influencing manifested in the direct interaction with the pupils whereas the possibilities to influence for the principal and education experts were more indirect. Some of the most important possibilities to influence for all the interviewees were through raising awareness and understanding, maintaining discussion about sustainability topics, and encouraging ESD activities. Furthermore, the small things in everyday life and acting as an example were often experienced the most effective ways to influence the ESD in schools. The biggest limitations to the professional agency for teachers, principals, and education experts were created by the lack of time, money, and resources, as well as the need for prioritizing other topics over ESD. The teachers’ professional agency was supported by their autonomy and independency. Moreover, one of the strongest supporting factors for all the interviewees were their colleagues and other professional networks. However, the teachers wished for more time and opportunities for collaboration as well as clearer learning materials for ESD. The principal hoped for a more active input from the local actors in creating collaboration around ESD topics, whereas the education experts discussed the lack of national coordination of ESD, and hoped for a transformation in which ESD would be the centre of the focus rather than an aspect separately implemented in the education systems. Future research should examine how to support the needed change in society and the education system in Finland to achieve sustainability.
Keywords: Education for Sustainable Development, Professional Agency, Sustainable Development, Sustainable Development Goals